2005
DOI: 10.1159/000085390
|View full text |Cite
|
Sign up to set email alerts
|

Kolorektale Karzinome: Neue Entwicklungen in der Tumorprävention und in der Diagnostik der Tumorausbreitung

Abstract: Kolorektale Karzinome entwickeln sich typischerweise über eine Adenom-Karzinom-Sequenz. Die lange Latenz der Karzinomentwicklung ermöglicht die gezielte Einflussnahme auf bekannte Risikofaktoren und die Früherkennung der Erkrankung in einem kurativ behandelbaren Stadium. Die Veränderung «typischer westlicher» Lebensgewohnheiten stellt eine erwiesene Maßnahme zur Prävention des kolorektalen Karzinoms dar. Nach gegenwärtiger Datenlage sind regelmäßige körperliche Bewegung, eine vitamin- und ballaststoffreiche Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…In a retrospective review of 226 patients from the Mayo Clinic, 37% of the polyps became larger during a mean follow-up period of 68 months, 21 of which progressed to invasive carcinoma in the 9-year follow-up. Another analysis showed that the cumulative risk for the diagnosis of cancer from a polyp at the 5th, 10th, and 20th year was 2.5, 8, and 24%, respectively [27]. We believe that even at the lowest reported range (i.e.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In a retrospective review of 226 patients from the Mayo Clinic, 37% of the polyps became larger during a mean follow-up period of 68 months, 21 of which progressed to invasive carcinoma in the 9-year follow-up. Another analysis showed that the cumulative risk for the diagnosis of cancer from a polyp at the 5th, 10th, and 20th year was 2.5, 8, and 24%, respectively [27]. We believe that even at the lowest reported range (i.e.…”
Section: Discussionmentioning
confidence: 80%
“…10%), the risk of a diminutive polyp being neoplastic is unacceptably high, and, therefore, the polyp should be totally excised and patients followed up regularly. There is strong evidence that removing colonic polyps reduces cancer mortality [27]. In the National Polyp Study, the incidence of CRC was compared with 3 reference groups consisting of 2 charts in which colonic polyps were not removed [28].…”
Section: Discussionmentioning
confidence: 99%